Facile synthesis of reduced graphene oxide–gold nanohybrid for potential use in industrial waste-water treatment. Issue 1 (1st January 2016) - Kar, Prasenjit; Sardar, Samim; Liu, Bo; Sreemany, Monjoy; Lemmens, Peter; Ghosh, Srabanti; Pal, Samir Kumar
Abstract: Here, we report a facile approach, by the photochemical reduction technique, for in situ synthesis of Au-reduced graphene oxide (Au-RGO) nanohybrids, which demonstrate excellent adsorption capacities and recyclability for a broad range of dyes. High-resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) data confirm the successful synthesis of Au-RGO nanohybrids. The effect of several experimental parameters (temperature and pH) variation can effectively control the dye adsorption capability. Furthermore, kinetic adsorption data reveal that the adsorption process follows a pseudo second-order model. The negative value of Gibbs free energy (ΔG 0 ) confirms spontaneity while the positive enthalpy (ΔH 0 ) indicates the endothermic nature of the adsorption process. Picosecond resolved fluorescence technique unravels the excited state dynamical processes of dye molecules adsorbed on the Au-RGO surface. Time resolved fluorescence quenching of Rh123 after adsorption on Au-RGO nanohybrids indicates efficient energy transfer from Rh123 to Au nanoparticles. A prototype device has been fabricated using Au-RGO nanohybrids on a syringe filter (pore size: 0.220 μm) and the experimental data indicate efficient removal of dyes from waste water with high recyclability. The application of this nanohybrid may lead to the development of an efficient reusable adsorbent in portable water purification. Abstract : UF0001